Analisis Penggunaan Istilah dalam Penulisan Berita pada Website Universitas Ahmad Dahlan - Arif Nur Fawaid, Muhammad; Wijayanti, Dedi (J-LELC: Journal of Language Education, Linguistics, and Culture, 2023)
The development of mass media in Indonesia today can be said to be very rapid. This can be seen from the emergence of various kinds of media, both print and electronic, that are developing in the midst of society. The media as a source of information must present information clearly. Clear in this case is clear in the news information and clear in the use of language. In line with this opinion. This study aims to determine the use of terms in news published on the UAD website. This research is descriptive qualitative research. The subject of this research is the use of terms used in the news on the UAD website. The data collection method used is the Simak, Gratis, Liba, Cakap (SBLC) method. There are two formulations that will be answered in this research; (1) how are the terms used in the UAD website; (2) What are the factors that cause the emergence of the term. This research produces written data. The results of the study show that there are 136 types of words with a total of 136 data, each consisting of 92 general term data and 44 special term data. Related to the factor of the use of terms, there are 116 accuracy data, 18 summary data and 2 data according to linguistic conventions. The dominant term factor used is the accuracy factor.